PEMBERANTASAN TINDAK PIDANA PERDAGANGAN ORANG - Mohammad Taufik Makarao (Jurnal Program Pascasarjana Ilmu Hukum Universitas Islam As-Syafi'iyah, 2019)
Eradication of Criminal Acts Trafficking in persons is a problem that does not only occur in Indonesia but has also become an international problem, and involving many people is therefore an organized crime. Crime of Trafficking in Persons has been regulated in legislation including Law No. 39 of 1999 concerning Human Rights, LAW OF THE REPUBLIC OF INDONESIA NUMBER 7 OF 1984 CONCERNING CERTIFICATION OF CONVENTIONS ON ELIMINATION OF ALL DISCIRIMINATION FOR WOMEN. LAW OF THE REPUBLIC OF INDONESIA NUMBER 23 OF 2002 CONCERNING CHILDREN'S PROTECTION, WHICH IS CHANGED BY LAW OF THE REPUBLIC OF INDONESIA NUMBER 35 OF 2014, Criminal Code (KUHP), and Law No. 21 of 2007 concerning Eradication of Crime in Trafficking in Persons. Even though it has been regulated following the sanctions, the criminal act of trafficking still continues to this day, this is inseparable from various factors including the occurrence not only in urban areas but also in looking for victims from rural areas, generally underage children and women, factors poverty, education factors, family factors, and others.